Nuts as a Part of Dietary Strategy to Improve Metabolic Biomarkers: A Narrative Review - Khalili, Leila; A-Elgadir, Thoraya Mohamed Elhassan; Mallick, Ayaz Khurram; El Enshasy, Hesham Ali; Sayyed, R. Z. (Frontiers in Nutrition, 2022)
Background: Nuts are in the spotlight because of their association with improved health outcomes. We aimed to summarize the findings of previous studies to assess the impact of nuts consumption on glycaemic and lipid profile, inflammation, and oxidative stress. Methods: Electronic searches for observational and intervention studies were undertaken in PubMed, Embase, Web of Science, and Science Direct for searching the studies aiming the application of different types of nuts and the beneficial effects of nuts in improving glycemia dyslipidemia, inflammation, and oxidative stress. Results: Results from 56 interventional, nine narrative and three systematic reviews, and 12 meta-analysis studies, aiming at the evaluating beneficial effects of different types of nuts on metabolic markers, showed that nut consumption could improve metabolic markers, including glycemic factors, lipid profile, and inflammatory and oxidative stress parameters in both healthy and subjects and individuals with metabolic disorders in a type-, dose- and duration-dependent manner. According to their unique nutrient profile, nuts can be part of a diet that features multiple healthy foods, resulting in improved glycemic response, lipid profile, oxidative stress, and inflammation. Conclusion: Considering nuts the efficacy of nuts in improving metabolic markers, incorporating nuts into the diet may prevent the incidence or aggravation of chronic metabolic diseases. Considering the health benefits of the nuts’ components, including essential micronutrients, if consumed in the appropriate dose and duration to provide the necessary amount of adequate micronutrients to improve health, we will see an improvement in metabolic factors. At the same time, more research is required to determine the optimal type, dose, and duration of nut intervention regarding metabolic control and reducing the risk of developing metabolic disorders.